Bioactivity of human Menopausal Gonadotrophin (hMG) and Deglycosylated hMG (hMGdG) from Urine of Post-Menopausal Women On invitro Bovine Embryonic cleavage - Hermadiv, Herry Agoes (KnE Life Sciences, 2017)
The aim of this study was to produce hMG from the uterus of post-menopausal women and to evaluate the influence of glycan removal from hMG glycoprotein molecule underwent deglycosylation (hMGdG) on the onset of in vitro bovine embryonic cleavage. The study identified hMG from the uterus of post-menopausal women by confirmation of the glycoprotein characteristic, examined the biochemical characteristics of deglycosylated hMG using N-glycanase and determined the influence of deglycosylated hMG on the onset of in vitro bovine embryonic cleavage. Urine samples were collected from 30 post-menopausal women. The results of SDS-PAGE demonstrated that the protein bands ranged between 19.4 and 107 kDa. Western blot revealed immune-reactivity of the 30 kDa band, which was a glycoprotein. The concentration of glycoprotein was 99860.00 ug/ml (PAS), the protein was 66939.29 µg/ml (Biuret) and carbohydrate 32920.71 µg/mL (PAS). The glycoprotein, protein and carbohydrate ratio within the hMG molecule was 3:2:1. Chemical characteristic of hMG following enzymatic deglycosylation using N-glycanase reduced the molecular weight to 26 kDa. The deglycocylated hMG reduced the onset of in vitro cleavage of bovine embryo from 24 to 20 hours (p < 0.01). Keywords: hMG, hMGdG, embryo cleavage, glycoprotein, deglycocylation, in vitro